(untitled) (CAHIERS MAGELLANES-NS, 2024)
This research paper embarks on a comprehensive examination of the portrayal of the Metaverse in ancient literature. Coined in the 1990s, the Metaverse represents a virtual shared space born from the convergence of physical and virtual reality, captivating modern audiences in science fiction and gaming. However, this study delves into the historical roots of the Metaverse concept, revealing its presence in ancient literary works, including The Epic of Gilgamesh, The Odyssey, The Divine Comedy, and The Ramayana. Drawing on a diverse range of literary theories and approaches, the paper meticulously analyzes the themes and motifs related to the Metaverse in these ancient narratives while simultaneously comparing them to contemporary Metaverse-based literature. Intricately weaving historical and cultural context into the analysis, the research sheds light on the social perspectives and beliefs that influenced the depiction of the Metaverse in different ancient civilizations. By contextualizing these portrayals, the paper provides invaluable insights into how virtual shared spaces were envisioned and embraced by diverse cultures in antiquity. The inclusion of The Ramayana in the study enriches our understanding of the concept's cultural interpretations, offering unique perspectives on interconnected realms and virtual dimensions. This meticulous exploration unearths the enduring appeal of the Metaverse concept throughout human history, transcending geographical and temporal boundaries. By scrutinizing the ancient texts, the research emphasizes that the idea of a virtual shared space has been an integral part of human imagination for centuries, resonating with both past and present generations. A deeper comprehension of the Metaverse's origins in ancient literature ultimately enriches our understanding of modern Metaverse-based literature, fostering a profound appreciation for the continuity of this captivating concept across the ages.